Cubed root of x

Cubed root of x

Input
cuberoot(x)
Result
x^(1/3)
Alternate form assuming x>0
x^(1/3)
Root
x = 0
Series expansion at x=0
piecewise | piecewise | -(-x)^(1/3) + O(x^13) | Im(x)<=0 -(-x)^(1/3)^* + O(x^13) | (otherwise) | x<=0 x^(1/3) + O(x^(37/3)) | (otherwise)
Series expansion at x=∞
piecewise | x^(1/3) + O((1/x)^(37/3)) | 1/x>0
-(-x)^(1/3) + O((1/x)^13) | (otherwise)
Derivative
d/dx(cuberoot(x)) = 1/(3 x^(1/3)^2)
Indefinite integral
integral cuberoot(x) dx = (3 x x^(1/3))/4 + constant

Leave a Reply

Your email address will not be published. Required fields are marked *